Experimental and Numerical Investigation of Clinched Joints Under Shear Tensile Loading at High Strain Rates - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Influence of plastic orthotropy on clinching of sheet metal - Friedlein, Johannes; Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, L.; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, M. (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Development of a Modified Punch Test for Investigating the Failure Behavior in Sheet Metal Materials - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)

Experimental and numerical investigation of the influence of multiaxial loading conditions on the failure behavior of clinched joints - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Joining of multi-material structures using a versatile self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Production Engineering)
Due to the increasing use of multi-material constructions and the resulting material incompatibilities, mechanical joining technologies are gaining in importance. The reasons for this are the variety of joining possibilities as well as high load-bearing capacities. However, the currently rigid tooling systems cannot react to changing boundary conditions, such as changed sheet thicknesses or strength. For this reason, a large number of specialised joining processes have been developed to expand the range of applications. Using a versatile self-piercing riveting process, multi-material structures are joined in this paper. In this process, a modified tool actuator technology is combined with multi-range capable auxiliary joining parts. The multi-range capability of the rivets is achieved by forming the rivet head onto the respective thickness of the joining part combination without creating a tooling set-up effort. The joints are investigated both experimentally on the basis of joint formation and load-bearing capacity tests as well as by means of numerical simulation. It turned out that all the joints examined could be manufactured according to the defined standards. The load-bearing capacities of the joints are comparable to those of conventionally joined joints. In some cases the joint fails prematurely, which is why lower energy absorptions are obtained. However, the maximum forces achieved are higher than those of conventional joints. Especially in the case of high-strength materials arranged on the die side, the interlock formation is low. In addition, the use of die-sided sheets requires a large deformation of the rivet head protrusion, which leads to an increase in stress and, as a result, to damage if the rivet head. However, a negative influence on the joint load-bearing capacity could be excluded.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Numerical Investigation of the Influence of a Movable Die Base on Joint Formation in Semi-tubular Self-piercing Riveting - Kappe, Fabian; Wituschek, Simon; de Pascalis, Vincenzo; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Materials Design and Applications IV)
Due to economic and ecological requirements and the associated trend towards lightweight construction, mechanical joining technologies like self-piercing riveting are gaining in importance. In addition, the increase in lightweight multi-material joints has led to the development of many different mechanical joining technologies which can only be applied to join a small number of material combinations. This leads to low process efficiency, and in the case of self-piercing riveting, to a large number of required tool changes. Another approach focuses on reacting to changing boundary conditions as well as the creation of customised joints by using adaptive tools, versatile auxiliary joining parts or modified process kinematics. Therefore, this study investigates the influence of increased die-sided kinematics on joint formation in self-piercing riveting process. The aim is to achieve an improvement of the joint properties by superimposing the punch feed. Furthermore, it is intended to reduce required tool changes due to the improved joint design. The investigations were carried out by means of a 2D-axisymmetric numerical simulation model using the LS-Dyna simulation software. After the validation of the process model, the die was extended to include driven die elements. Using the model, different kinematics as well as their effects on the joint formation and the internal stress concentration could be analysed. In principle, the increased actuator technology enabled an increase of the interlock formation for both pure aluminium and multi-material joints consisting of steel and aluminium. However, the resulting process forces were higher during the process phases of punching and spreading.

Increasing flexibility of self-piercing riveting by reducing tool–geometry combinations using cluster analysis in the application of multi-material design - Kappe, Fabian; Schadow, Luca; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers Part L Journal of Materials Design and Applications)

Determining the properties of multi‑range semi‑tubular self‑piercing riveted joints - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson (Production Engineering)

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)
The application of the mechanical joining process clinching enables the joining of sheet metals with a wide range of material-thickness configurations, which is of interest in lightweight construction of multi-material structures. Each material-thickness combination results in a joint with its own property profile that is affected differently by variations. Manufacturing process-related effects from preforming steps influence the geometric shape of a clinched joint as well as its load-bearing capacity. During the clinching process high degrees of plastic strain, increased temperatures and high strain rates occur. In this context, a 3D numerical model was developed which can represent the material-specific behaviour during the process chain steps sheet metal forming, joining, and loading phase in order to achieve a high predictive accuracy of the simulation. Besides to the investigation of the prediction accuracy, the extent of the influence of individual modelling aspects such as temperature and strain rate dependency is examined.

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, Lars; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, Martina (Production Engineering)
Abstract In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

A Review on the Modeling of the Clinching Process Chain - Part II: Joining Process - Schramm, Britta; Friedlein, Johannes; Gröger, Benjamin; Bielak, Christian Roman; Bobbert, Mathias; Gude, Maik; Meschut, Gerson; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)